Effect of Film Thickness on Resistance to Permanent Deformation in Asphalt Mixtures - Eva Remišová (The Baltic Journal of Road and Bridge Engineering)
The resistance of asphalt mixtures against permanent deformation is one of important requirements that have to be verified in the design process of asphalt mixtures. In the case of asphalt concrete the European Standard  EN 13108-1:2006 Bituminous Mixtures. Material Specifications. Part 1: Asphalt Concrete allows empirical (compositional recipes and requirements) or fundamental approach for testing of permanent deformation resistance. A fundamental approach specifies asphalt concrete in terms of performance-based requirements linked to limited prescription of composition and constituent materials. In this design approach a triaxial cyclic compression test is used to verify resistance to permanent deformation. The presented study investigates characteristics of resistance to rutting of asphalt concrete mixtures (eight mixtures of AC 11 from different producers) determined by triaxial cyclic compression test. The basic conclusions and statements of main factors influenced resistance to rutting (type of binder, binder content, and aggregate gradation) have been worked out from prevenient experience and experimental measuring. But measured test results presented in the following paper point out differences in resistance however the bitumen contents are relatively the same. During detailed investigation the tested asphalt mixtures had small differences in aggregate gradation. Changes in gradation make change of aggregate specific surface and the mixture needs different bitumen content to coat aggregate particles, to bound them to each other and to make stiff material resistant to rutting. The results from measuring of resistance to permanent deformation show the relation between aggregate specific surface and bitumen film thickness and permanent deformation.